19.yy Başından Cumhuriyetin Kuruluşuna Kadar Olan Süreçte Beyoğlu ve Çevresinde Meydana Gelen Yangınların Galata Sarayı’nın Değişimine Etkileri. - Balcı, Öykü Bahar; Kolay, Mehmet Sinan (Electronic Turkish Studies, 2020)
Galata Sarayı (Galata Palace), later known as Mekteb-i Tıbbiye, Mekteb-i Sultani or Galatasaray High School, has undergone many structural changes throughout the history of five hundred years as an educational institution. It is determined that most of these reconstructions occurred due to the fires in the region. The aim of this article, after determining the dates of the fires that affected the building, is to ascertain the construction activities and the structural changes they caused in the building. Since most of the documents dates to the 19th and 20th centuries, the study is limited to the construction activities in this period. First of all, in the scope of the historical process, the historical background of Galata Sarayı from its foundation to the present day and the fires occurred in Beyoğlu and its surroundings after 17th century in parallel to the settlement process of Beyoğlu in 17th century have been examined. The construction activities as a result of the fires of 1817, 1831 and 1848 in the region and the 1907 fire occurred inside the school, which caused damage to the Galata Sarayı; are analyzed in detail through archival documents, travelers’ notes, journals, maps of the period, drawings and old photographs. In the view of the data provided by the sources, the construction activities in the period after the half of the 19th century could be evaluated on a more detailed scale. The greatest change in the structure took place during the reconstruction process in 1862 after the 1848 fire that occurred during the period of Mekteb-i Tıbbiye. This situation is in line with Beyoğlu's masonry reconstruction process. The structure was also compared with examples with similar functions and plan schemes in the context of Ottoman architecture under the influence of the West in the 19th century.